Selection of Lower Electrode for Single-Sided Resistance Spot Welding of Carbon Steel Tube STKM 13A and Cold Rolled Carbon Steel Sheet SPCC - Khuenkaew, Teerawut; Mhoraksa, Thiti; Jattakul, Prajak; Mapakhe, Thunyalak; Saengsawang, Suriyate; Thawornsiri, Kreakrit; Insorn, Withaya (Journal of Manufacturing & Management Technology, 2022)
The objective of this research is to select the geometry of the lower electrode tip used in the single-sided resistance spot welding of weldments between carbon steel tube STKM 13A with a 12.7 mm outer diameter and 1.4 mm of thickness and cold rolled carbon steel sheet SPCC with 1.2 mm of thickness. The spot was welded using a 50 kVA AC, 50 Hz RSW machine, while the quality of the weld was assessed by considering the weldment visual examination and nugget diameter. The results of the study explained the weldment appearance of both the top surfaces of SPCC and the surface of the tube STKM 13A. The electrode geometry type 3 is where the arc area of the electrode is the support area for the pipe during welding. optimal physical appearance without arcing on the pipe surface. The average nugget diameter was 6.018 mm, which meets the JIS Z3140 standard.